2017
DOI: 10.1161/strokeaha.117.018773
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Non-Vitamin K Antagonist Oral Anticoagulants in Asian Patients With Atrial Fibrillation

Abstract: In real-world practice among a high-risk Asian atrial fibrillation population, all 3 NOACs demonstrated similar risk of ischemic stroke and lower risk of ICH compared with warfarin. All-cause mortality was significantly lower only with dabigatran and apixaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 29 publications
8
112
2
Order By: Relevance
“…Apixaban had the shortest mean following‐up period of only 0.76 years due to its introduction later to the market in Taiwan. Although the follow‐up period of apixaban was limited in our present study, our results were compatible with the latest result of Cha et al, showing that apixaban showed a trend of lower risk of IS (HR, 0.67; 95% CI, 0.35–1.17), a significantly lower risk of intracranial hemorrhage (HR, 0.30; 95% CI, 0.09–0.70) and all‐cause mortality (HR, 0.32; 95% CI, 0.18–0.53) compared to warfarin in Koreans with NVAF 11. Nevertheless, enrollment of more patients and longer follow‐up periods are necessary to demonstrate the efficacy and safety of Asians taking apixaban in the future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Apixaban had the shortest mean following‐up period of only 0.76 years due to its introduction later to the market in Taiwan. Although the follow‐up period of apixaban was limited in our present study, our results were compatible with the latest result of Cha et al, showing that apixaban showed a trend of lower risk of IS (HR, 0.67; 95% CI, 0.35–1.17), a significantly lower risk of intracranial hemorrhage (HR, 0.30; 95% CI, 0.09–0.70) and all‐cause mortality (HR, 0.32; 95% CI, 0.18–0.53) compared to warfarin in Koreans with NVAF 11. Nevertheless, enrollment of more patients and longer follow‐up periods are necessary to demonstrate the efficacy and safety of Asians taking apixaban in the future.…”
Section: Discussionmentioning
confidence: 93%
“…However, the follow‐up periods and patient numbers in those real‐world studies were limited, and the efficacy and safety profiles of apixaban were lacking. As we know, there has been only 1 publication that directly compares the efficacy and safety of all 3 NOACs (ie, apixaban, dabigatran, and rivaroxaban) in a limited number of Asians with AF 11. The objective of this study was to compare the efficacy and safety of apixaban, dabigatran, and rivaroxaban with warfarin in Asians with NVAF as a nationwide retrospective cohort study with an extended follow‐up period.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors have been shown to affect bleeding events . Studies ranging from observational studies, randomized control trials along with several meta‐analyses have shown that Asians are prone to bleeding more than other racial groups . Poor anticoagulation control and genetic factors have been highlighted as the main reasons.…”
Section: Discussionmentioning
confidence: 99%
“…While there are a large number of published reports evaluating the incidence, risk factors, and outcomes of warfarin‐associated major bleeding (WAMB), almost all of those reports were from the developed countries. Some data on WAMB in Asian population have been published as a subanalysis of large, randomized, controlled trials comparing NOACs versus warfarin or from registries . However, these data were derived only from non‐valvular atrial fibrillation (NAVF) patients while patients using warfarin for other important indications were not included.…”
Section: Introductionmentioning
confidence: 99%
“…This raises concerns regarding hemorrhagic events and therapeutic anticoagulative effects. Encouragingly, recent studies have indicated that a reduced dosage (dabigatran 110 mg twice daily or rivaroxaban 10 mg once daily) could have a similar stroke prophylactic effect in the Asian population . Based on the present evidence, we generally prescribe reduced dosages to patients with a relatively high risk of bleeding.…”
Section: Discussionmentioning
confidence: 76%